Teaching reform and practice based on OBE concept: Taking the course of Python programming and practice as an example - Gu Cuihong; Zheng Xinghua; Li Guangyan (SHS Web of Conferences, 2023)
Python Programming and Practice is a professional course for computer related majors. Through teaching practice, and based on OBE (Outcome-based Education) concept of course reform, we have revised the course syllabus, reformulated the teaching plan, standardized the classroom teaching, adopted online and offline mixed teaching model to teach the basic knowledge online, and to teach with project case method in offline classroom teaching. The course is completely transformed into outcome-based teaching, which improves the depth and breadth of the course teaching, and improves the students’ practical ability.